Metformin discontinuation in patients beginning second-line glucose-lowering therapy: results from the global observational DISCOVER study programme - Khunti, Kamlesh (BMJ Open, 2020)
OBJECTIVES: To evaluate the extent to which patients with type 2 diabetes discontinue metformin therapy when initiating second-line treatment and factors associated with metformin discontinuation, using baseline data from the DISCOVER study programme. DESIGN: DISCOVER is a 3-year, prospective, observational study programme including data from 38 countries across 6 continents from 2014 to 2019. SETTING: Primary and secondary healthcare centres, hospitals and specialist diabetes centres in both urban and rural locations. PARTICIPANTS: A total of 15 992 patients with type 2 diabetes initiating second-line glucose-lowering therapy. PRIMARY AND SECONDARY OUTCOME MEASURES: The proportion of patients who discontinued metformin as a second-line therapy and the factors associated with this treatment change. RESULTS: Of the 14 668 patients (from 37 countries) with valid treatment data, 11 837 (80.7%) received metformin as first-line glucose-lowering therapy; 8488 (71.7%) received metformin monotherapy and 3349 (28.3%) received metformin as part of a combination therapy. Overall, treatment with metformin was discontinued in 15.1% (1782) of patients who received first-line metformin (14.1% (1194) and 17.6% (588) in those who received metformin as monotherapy and as part of a combination, respectively); this proportion varied across regions from 6.9% (54) in Africa to 20.6% (628) in South-East Asia. On metformin discontinuation, 73.6% (1311) of patients received a non-insulin monotherapy at second line. Factors associated with an increased odds of metformin discontinuation were older age (≥75 years) and having a history of chronic kidney disease. The probability of metformin monotherapy discontinuation was lower in patients from Africa than in those from Europe. CONCLUSIONS: A substantial number of patients discontinued taking metformin when beginning second-line therapy. Most of these patients subsequently received a non-insulin monotherapy at second line, in contradiction to international guidelines and potentially leaving them at an increased risk of hyperglycaemia and associated adverse outcomes. TRIAL REGISTRATION NUMBERS: NCT02322762 and NCT02226822.